Wybory biskupów w świetle korespondencji Grzegorza Wielkiego - Lewandowicz, Janusz (Vox Patrum, 2010)
Having presented briefly the context in which the Church found herself, as well as the criteria required of candidates to episcopacy, the author discusses problems related to the promotion of bishops, based on selected examples extracted from the correspondences of Pope Gregory the Great. It shows that His Holiness was aware of the significant role played by episcopal elections in the Church’s life. His interventions in this matter were to ensure that local sees were assigned to appropriate candidates, i.e. those of good reputation, outstanding in good morals and possessing the expertise required in Sacred Scriptures and Catholic doctrines. Procedures implemented by Pope Gregory the Great with the aim of achieving this goal involved, amongst other things gathering information about the candidates to the episcopacy as well as the inclusion of the entire local clergy and all the lay faithful in the electoral process. Such a policy undertaken by His Holiness in promoting episcopates was aimed at strengthening their ties with the Holy See. This proved to be influential, especially during the institutional and structural destruction in Western Italia and threats from the Lombards, who wanted to destroy the well-established traditional Roman order. To avoid all forms of manipulation by lay persons in ecclesiastical matters, this policy excluded the possibility of promoting a layman to the episcopacy. Where there were difficulties in solving electoral issues, Gregory the Great often personally appointed candidates from the local clergy or from the Roman clergy. Pope Gregory the Great also reserved the right of preconisation of the elected bishops.